Case Report: Life-Saving Emergency Gastrointestinal Endoscopy (Pulse, 2025)
Background: Acute upper gastrointestinal bleeding is the most common gastrointestinal emergency, and the patients should undergo urgent endoscopy within 24 hours of presentation, especially when associated with significant comorbidity. Accurate endoscopic diagnosis and effective therapeutic intervention with full endoscopy set up is the key to success for rescuing the patients from life threatening situations. Case Presentation: A 65-year-old Bangladeshi male, admitted with acute myocardial infarction at Evercare Hospital Dhaka, suddenly started vomiting out of profuse amounts of fresh blood in Cardiac Cath Lab during Coronary intervention and was brought back to CCU. On urgent referral we took a full set of endoscope machines with necessary equipment to CCU. Owing to the possibility of aspiration of blood, a cardiac anesthetist did endotracheal intubation to seal the entry of airway. Endoscopic evaluation revealed a deep mucosal tear at lower esophagus, secondary to reflux. After irrigation with diluted epinephrine, four metallic clips were applied and hemostasis ensured. One more clip was applied to the remaining defect of the tear after 3 days at follow-up endoscopy. The patient fully recovered from GI bleeding and discharged in stable condition. Conclusion: This case demonstrates the life-saving potential of emergency endoscopic procedures in managing complex upper gastrointestinal bleeding. It also highlighted the importance of advanced skills, creativity and multidisciplinary expertise in overcoming procedural challenges.Pulse Vol.17, 2025 P: 41-43